Respon Pupuk Kalium dan Ukuran Umbi Bibit Terhadap Pertumbuhan dan Produksi Kentang (Solanum tuberosum): Response of Potassium Fertilizer and Seed Tuber Size on The Growth and Production of Potato (Solanum tuberosum) - Olivia Cindowarni; Damsir (Planta Simbiosa, 2023)
Potato is one of vegetables that has a lot of nutritional content. Potatoes contain the main source of carbohydrates, which are useful to increase energy and metabolic processes in the human’s body. This study aims to determine the response of potassium fertilizer (KCl) with different sizes of seed tuber on growth and production of potatoes. This research was conducted in three locations, namely the Horticultural Seed Center (BBIH) grounds, the Faculty of Basic Sciences Laboratory, and the Seed and Breeding of Plant Laboratory. The planting material used in this study was potato seed of the Granola G1 variety, the seed came from a potato seed producer in Lembang, West Java. This study used a factorial randomized block design (3x4). The factorial treatment consisted of two factors, the first factor was seed size (B) and the second factor was potassium fertilizer’s dose (K). Potassium fertilizer (KCl) and various sizes of seed tubers responded to the green level of leaves, plant height, wet weight of stover, amount of tubers, and tuber weight. The combination of potassium fertilizer (KCl) 30 kg ha-1 and large tuber size (±16.02 g) affected the growth and production of potato (Solanum tuberosum L.).